Bethe ansatz for the deformed Gaudin model - Kulish, Petr (2018)
A deformation of the sl(2) Gaudin model by a Jordanian r-matrix depending on the spectral parameter is constructed. The energy spectrum is preserved and recurrent creation operators are proposed.